Psychometric properties of the Turkish version of the Revised Child Anxiety and Depression Scale – Child Version in a clinical sample - Vahdet Gormez; Ayse Kılınçaslan; Abdurrahman Cahid Orengul; Chad Ebesutani; Ilyas Kaya; Veysi Ceri; Serhat Nasıroglu; Mekiya Filiz; Bruce Chorpita (Psychiatry and Clinical Psychopharmacology, 2017)
Objective: The shortage of cross-culturally validated instruments limits the study and treatment of psychopathology in countries other than English-speaking ones. The Revised Child Anxiety and Depression Scale – Child Version (RCADS-CV) is a self-report questionnaire that assesses dimensions of DSM anxiety and depressive disorders in youths. In this present study, we aimed to examine the psychometric properties of the Turkish version of the RCADS-CV in a clinical sample of children in Turkey. Method: The participants were 483 children aged 8–17 years old. Subjects were recruited from the following centers: Bezmialem University Hospital (55.7%), Kütahya Regional Hospital (17.4%), Istanbul Medical Faculty Hospital of the Istanbul University (16.7%), and Sakarya University Hospital (12.2%). A semi-structured diagnostic interview was carried out and the following measures were used: Children’s Depression Inventory, Screen for Child Anxiety-Related Emotional Disorders (SCARED), and Strengths and Difficulties Questionnaire (SDQ). Results: Inter-scale reliability was strong/excellent with a Cronbach’s α of .95 and coefficients for the RCADS-CV subscales ranging from .75 to .86, demonstrating good internal consistency. Convergent and discriminant validity tests against both a semi-structured clinical interview and self-report measures suggested favorable properties. Confirmatory factor analysis supported the original six-factor model. RCADS-CV showed greater correspondence to specific diagnoses in comparative tests with the existing measures of anxiety and depression. Conclusion: Overall, the study provides satisfactory evidence that the Turkish RCADS-CV yields valid scores for clinical purposes among Turkish children.